Neurophysiology Intraoperative Monitoring (Niom) pada Operasi Deformitiy Correction at Adolesent Scoliosis - Herlambang, Panji; Sudadi; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
The use of neurophysiological intraoperative monitoring (NIOM) during spinal orthopaedic and neurosurgical procedures provides a challenge to the attending anaesthesiologist. Since all anaesthetic agents affect synaptic function, the choice of agent will be determined by the type of surgery and the NIOM modality employed. Had been performed surgery for scoliosis correction of spinal abnormalities in children aged 15 years with using of sensory and motoric NIOM. The surgery going under general anesthesia with the installation monitor invasive arterial line and central venous pressure during surgery for hemodynamic monitoring. Drugs used during anesthesia using balanced anesthesia technique with a combination of opioids, propofol and sevoflurane as inhalation. Muscle relaxants given intermittently for operator leisure and ventilation controls. Postoperative hospitalization in ICU with the aim of assessing the function of the respiratory and neurological of the patients and pain management.